Автоматизація процесів технічного обслуговування та ремонту річкових суден з використанням методів виробничої логістики - Дакі, О. А.; Daki, O.; Даки, Е. А. (ЦНТУ, 2020)
У статті розглянуто роль виробничої логістики у рішенні завдання технічного обслуговування та ремонту суден. Розроблено моделі автоматизації процесів технічного обслуговування та ремонту річкових суден з використанням методів виробничої логістики. Комплексна автоматизація виробничих процесів веде до підвищення ефективності діяльності підприємства, особливо це позначається на етапі планування і визначення потреб у матеріалах, вузлах, агрегатах як власного виробництва, так і покупних.The article is devoted to the development of models for automation of maintenance and repair of river vessels using the methods of production logistics, as well as to determine the role of production logistics in solving the problem of maintenance and repair of vessels. Achieving this goal contributes to solving a number of problems of modern enterprise management. The research presented in the article is based on the work of domestic and foreign researchers. The production process is a set of interdependent actions of people, means of production and nature, necessary for the manufacture of products. The main component of the production process is the technological process - a set of actions to change and determine the state of the object of labor. Various production processes are carried out at the enterprises. Flow production is a highly efficient method of organizing the production process. Under the conditions of the flow, the production process is carried out in maximum accordance with the principles of its rational organization. In the conditions of crisis phenomena in the domestic economy, the fall of industrial production for ship repair enterprises, the question of replacing scarce and expensive materials for the organization of production, as well as rationing and careful use of existing materials became acute. Comprehensive automation of production processes leads to increased efficiency of the enterprise, especially at the stage of planning and determining the needs for materials, components, units, both own production and purchased. The application of production planning principles is very important for solving a number of problems related to the maintenance and repair of river vessels. Ways to solve this problem lie in the planes: reorientation of procurement in the domestic market; planning own production of scarce and expensive products for production needs; use of scientific methods of material flow organization using the principles of production logistics. В статье рассматривается роль производственной логистики в решении задания технического обслуживания и ремонта судов. Разработаны модели автоматизации процессов технического обслуживания и ремонта речных судов с использованием методов производственной логистики. Комплексная автоматизация производственных процессов ведет к повышению эффективности деятельности предприятия, особенно это отображается на этапе планирования и определения потребностей в материалах, узлах, агрегатах как собственного производства, так и покупных.
Automation of Processes of Maintenance and Repair of River Vessels Using Methods of Production Logistics
Автоматизация процессов технического обслуживания и ремонта речных судов с использованием методов производственной логистики
Keywords: автоматизація виробництва; виробничий процес; водний транспорт; логістика; ремонт та технічне обслуговування; automation of production; production process; water transport; logistics; repair and maintenance